The Realization of Interpersonal Meaning in Donald Trump’s 2020 Speeches (Universitas Negeri Semarang, 2021)
Interpersonal Metafunction of a speech refers to the way speakers and audiences establish and maintain the relations among themselves and influence their behaviors. Analyzing interpersonal meaning in speech is very useful to see how the speakers interact with the listeners. This research analyzed three speeches of Donald Trump’s 2020 speeches. It analyzed mood, modality, mood and modality relation, and the conceptual application of the findings toward English Language Teaching. It used the Systemic Functional Linguistics theory by Halliday and Matthiessen (2014). The result shows that Donald Trump mostly used a declarative mood to give American information as much as possible. Donald Trump mostly used the median degree of Inclination because his ability to protect the American people was not strong enough at the time because he and his people had not provided vaccines. In the mood and modality relationship, it was expressed the seriousness of the situation and prevention act, commitment, empathy, and encouragement. Further, the conceptual application of the findings toward English Language Teaching concluded that mood and modality are very useful in teaching writing because they can give them understanding and knowledge about grammatical features of Mood and modality.